Optimizing water-saving irrigation schemes for rice (Oryza sativa L.) using DSSAT-CERES-Rice model - Gao, Shikai; Gu, Qiongqiong; Gong, Xuewen; Li, Yanbin; Yan, Shaofeng; Li, Yuanyuan (International Journal of Agricultural and Biological Engineering, 2023)
Rice is one of the major crops in China, and enhancing the rice yield and water use efficiency is critical to ensuring food security in China. Determining how to optimize a scientific and efficient irrigation and drainage scheme by combining existing technology is currently a hot topic. Crop growth models can be used to assess actual or proposed water management regimes intended to increase water use efficiency and mitigate water shortages. In this study, a CERES-Rice model was calibrated and validated using a two-year field experiment. Four irrigation and drainage treatments were designed for the experiment: alternate wetting and drying (AWD), controlled drainage (CD), controlled irrigation and drainage for a low water level (CID1), and controlled irrigation and drainage for a high water level (CID2). According to the indicators normalized root mean square error (NRMSE) and index of agreement (d), the calibrated CERES-Rice model accurately predicted grain yield (NRMSE=6.67%, d=0.77), , shoot biomass (NRMSE = 3.37%, d = 0.77), actual evapotranspiration (ETa) (NRMSE = 3.83%, d = 0.74), irrigation volume (NRMSE = 15.56%, d = 0.94), and leaf area index (NRMSE = 9.69%, d = 0.98) over 2 a. The calibrated model was subsequently used to evaluate rice production in response to the four treatments (AWD, CD, CID1, and CID2) under 60 meteorological scenarios which were divided into wet years (22 a), normal years (16 a), and dry years (22 a). Results showed that the yield of AWD was the largest among four treatments in different hydrological years. Relative to that of AWD, the yield of CD, CID1, and CID2 were respectively reduced by 5.7%, 2.6%, 8.7% in wet years, 9.2%, 2.3%, 8.6% in normal years, and 9.2%, 3.8%, 3.9% in dry years. However, rainwater use efficiency and irrigation water use efficiency were the greatest for CID2 in different hydrological years. The entropy-weighting TOPSIS model was used to optimize the four water-saving irrigation schemes in terms of water-saving, labor-saving and high-yield, based on the simulation results of the CERES-Rice model in the past 60 a. These results showed that CID1 and AWD were optimal in the wet years, CID1 and CID2 were optimal in the normal and dry years. These results may provide a strong scientific basis for the optimization of water-saving irrigation technology for rice.Key words: CERES-Rice, controlled irrigation and drainage, water-saving, long-term weather data, water use efficiencyDOI: 10.25165/j.ijabe.20231602.7361Citation: Gao S K, Gu Q Q, Gong X W, Li Y B, Yan S F, Li Y Y. Optimizing water-saving irrigation schemes for rice (Oryza sativa L.) using DSSAT-CERES-Rice model. Int J Agric & Biol Eng, 2023; 16(2): 142-151.